Influence of photodynamic therapy on the level of matrix metalloproteinases in squamous cell skin cancer - V. V. Maslyakov; D. Yu. Grebnev; A. A. Tsymbal; L. M. Kim (Biomedical Photonics)
The effect of photodynamic therapy (PDT) on the level of matrix metalloproteinases in squamous cell skin cancer (SCSC) was studied. The study involved 202 people, including 185 patients with SCSC, who were on outpatient and inpatient treatment in medical institutions of Engels and Saratov during the period from 2015 to 2019, and 17 donors. The study design included studies in three main groups. The first (intervention) group included 74 (36.6%) patients with SCSC who underwent combined treatment, including PDT at the first stage and surgical treatment at the second stage. The second group consisted of 111 (55.0%) patients with SCSC who underwent only surgical treatment. The third group consisted of 17 (8.4%) relatively healthy volunteer donors, comparable in age and sex with the patients of the main group. As a result of the study, it was found that the level of metalloproteinase-1 inhibitor (TIMP-1) in the blood serum of patients with SCSC was reduced compared with physiologically normal indicators, which led to a statistically significant increase in matrix metalloproteinases (MMPs) MMPs-2, MMPs-7 and MMPs-9. Performing only surgical treatment for this pathology does not lead to a complete recovery of these indicators. However, the use of combined treatment including PDT showed a statistically significant increase in the amount of TIMP-1 before the start of surgical treatment, which naturally led to a decrease in MMPs-2, MMPs-7 and MMPs-9. Later, after excision of the tumor, the patients of this group had a complete normalization of TIMP-1, which, in turn, contributed to a decrease and then restoration of the number of MMPs-2, MMPs-7 and MMPs-9 to physiologically normal values.